Uji Aktivitas Antimikroba Ekstrak Etanol Daun Telang (Clitoria ternatea L.) Terhadap Mikroba Penyebab Infeksi Kulit - Azizah, Masayu; Ananda, Siska; Agung Sriwijaya, Reza (Jurnal Kesehatan Saelmakers PERDANA (JKSP), 2024)
Telang leaf is a plant species (Clitoria ternatea L.) and belongs to the Fabeaceae family. In this study, the antimicrobial activity of the ethanol extract of butterfly pea leaves (Clitoria ternatea L.) will be tested against microbes that cause skin infections. The method used in the antimicrobial activity test was the diffusion method using paper discs against the bacteria Staphylococcus epidermidis ATCC 12228, Propionibacterium acne ATCC 11827 dan jamur Trichophyton mentagrophytes ATCC 52016, Malassezia furfur ATCC 14521. The concentration of the ethanol extract of telang leaves used was 30%, 40%, and 50%. As a positive control for antibacterial using clindamycin, antifungi using ketoconazole and negative control using distillate ethanol. The test results showed that the ethanol extract from telang leaves has potential as an antimicrobial against bacteria and fungi. The measurement results of the largest inhibition diameter were at a concentration of 50% against Staphylococcus epidermidis ATCC 12228 obtained an inhibition zone of 10,33 mm, Propionibacterium acne ATCC 11827 obtained an inhibition zone of 10,03 mm, and the fungi Trichophyton mentagrophytes ATCC 52016 obtained an inhibition zone of 7,23 mm, Malassezia furfur ATCC 14521 obtained an inhibition zone of 8,23 mm